Swimming Sports: Parental Management In Children With Asthma - Vicki Ahmad Karisman; Yusup Nursyamsi (STKIP Muhammadiyah Kuningan, 2022)
This study aims to determine the management of parents through physical activity, in this case, swimming, to reduce asthma symptoms. This swimming activity is collaborated with other activities such as cycling, walking and running. This research method uses Qualitative Research with one participant who is a parent of asthmatics. The instrument used is an interview, and the data was analyzed using Health Literacy Theory. The results show that by managing health-literate parents, the program will impact reducing asthma symptoms in children